Initial clinical experience with [177Lu]Lu-PNT2002 radioligand therapy in metastatic castration-resistant prostate cancer: dosimetry, safety, and efficacy from the lead-in cohort of the SPLASH trial - Hansen, Aaron R.; Probst, Stephan; Beauregard, Jean-Mathieu; Viglianti, Benjamin L.; Michalski, Jeff M.; Tagawa, Scott T.; Sartor, Oliver; Tutrone, Ronald F.; Oz, Orhan K.; Courtney, Kevin D.; Delpassand, Ebrahim S.; Nordquist, Luke T.; et al. (Frontiers in oncology, 2025)
SPLASH (NCT04647526) is a multicenter phase III trial evaluating the efficacy and safety of [ Lu]Lu-PNT2002 radioligand therapy in metastatic castration-resistant prostate cancer (mCRPC). This study leveraged a lead-in phase to assess tissue dosimetry and evaluate preliminary safety and efficacy, prior to expansion into a randomized phase. Here we report those results. Enrolled participants had mCRPC that progressed on one prior androgen receptor pathway inhibitor (ARPI), were prostate-specific membrane antigen (PSMA) PET-positive as determined by a central reader, were chemotherapy-naïve for mCRPC, and had adequate bone marrow and end-organ reserve. Participants received up to 4 cycles of [ Lu]Lu-PNT2002 at 6.8 GBq (± 10%) intravenously per cycle every 8 weeks. Dosimetry (planar + SPECT/CT [n=7]; planar only [n=20]), safety, prostate-specific antigen (PSA) response, objective response rate (ORR), and radiographic progression-free survival (rPFS) per blinded independent central review were assessed. Of 34 individuals screened, 32 underwent PSMA-PET/CT; 27 met all eligibility criteria. Median (range) age was 72 (57-86) years; all participants were enrolled in North America; 40.7% initiated prior ARPI treatment without distant metastases (M0) and 25.9% while hormone sensitive. Nineteen of 27 (70.4%) participants completed all 4 planned cycles. Organs receiving the largest mean (median, range) specific absorbed doses were lacrimal glands at 1.2 (0.9, 0.4-6.7) Gy/GBq (planar only [n=27]), followed by kidneys at 0.73 (0.63, 0.22-1.8) Gy/GBq (planar + SPECT/CT [n=7]; planar only [n=20]). Mean (median, range) tumor specific absorbed dose was 4.3 (2.1, 0.3-33.4) Gy/GBq (approximately 29 Gy/cycle) based on planar + SPECT/CT of 21 lesions in seven participants. [ Lu]Lu-PNT2002 was associated with no treatment-related deaths, few treatment-related grade ≥3 treatment-emergent adverse events (TEAEs), and no discontinuations for unacceptable toxicity. Treatment-related TEAEs occurring in ≥10% of participants included dry mouth (22.2%; all grade 1), fatigue (18.5%; grades 1-2), nausea (18.5%; grades 1-2), and anemia (14.8%; grades 1-3). Median (95% CI) rPFS was 11.5 (9.2-19.1) months, a PSA decline of ≥50% occurred in 42.3% (11/26) of participants, and confirmed ORR for evaluable disease was 50% (5/10). [ Lu]Lu-PNT2002, administered at 6.8 GBq/cycle for 4 cycles, demonstrated a favorable dosimetry and safety profile, as well as promising preliminary efficacy. https://clinicaltrials.gov/, identifier NCT04647526.